Religie-onderwys in ’n Multi-religieuse Bedeling: Opvoederpersepsies en Realiteite (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2005)
A multi-religious curriculum for Religion Education will be implemented in South African schools from 2006. Practicing educators had not yet been retrained for this task. This article explores practicing educators’ assessment of their own basic knowledge, compared to their actual tested knowledge, of the five major religions of the world. The emphasis is put on educators’ basic knowledge about the various religions’, including religious dogmas, founder(s), books and symbols, as well as their equipment to facilitate Religion Education. Furthermore, educators’ preferences with respect to responsibilities for the facilitation of Religion Education are also explored. The research indicates that educators assess their own knowledge constantly lower than their actual tested knowledge. They know relatively little about the basic aspects of major religions (other than the Christian). It seems that it would take an enormous effort from various role players to equip educators in time for the implementation of the new curriculum at the start of 2006.